Sequencing of a modified oil red O development technique for the detection of latent fingermarks on paper surfaces - Frick, Amanda; Fritz, Patrick; Lewis, Simon; Van Bronswijk, Wilhelm (International Association for Identification, 2013)
A modified detection sequence is presented for the recovery of latent fingermarks on porous substrates. 1,2-Indanedione, Oil Red O (ORO) in propylene glycol, and physical developer (PD) were successfully used to develop recently deposited latent fingermarks when applied in the order given. The incorporation of ORO into the detection sequence increased the number of latent fingermarks that were detected compared to using the standard sequence of 1,2-indanedione followed by PD only.